Hormones and Auditory Perception: Study of Dichotic Listening in Women during the Menstrual Cycle - Carneiro, Cláudia da Silva; Almeida, Anna Alice Figueiredo de; Ribas, Angela; Kluk-De Kort, Karolina; Lima, Daviany Oliveira; Araújo, Aline Menezes Guedes Dias de; Ferreira, Danilo Augusto de Holanda; Martins, Mariana Lopes; Freitas, Thais Mendonça Maia Wanderley Cruz; de Rosa, Marine Raquel Diniz (International Archives of Otorhinolaryngology, 2019)
Introduction Dichotic listening refers to the ability to hear different sounds presented to each ear simultaneously.Objective The aim of the present study was to assess dichotic listening in women throughout the menstrual cycle.Methods The volunteers who met the eligibility criteria participated in a dichotic listening assessment composed of three tests: 1) staggered spondaic word test; 2) dichotic digits test; and 3) consonant-vowel test. The female participants were tested during two different phases of the menstrual cycle: the follicular (days 11 to 13) and luteal (days 23 to 26) phases. The phases were confirmed by measuring serum levels of the hormone estradiol.Results A total of 20 volunteers aged 18 to 49 years participated in the study (9 females and 11 males). In test 1, only the right ear of females showed better performance during the follicular phase (high estrogen levels), compared with the luteal phase (low estrogen levels); in test 2, there were no significant differences for any of the groups; and in test 3, both males and females showed significantly better performance in their right ear compared with their left ear.Conclusion The better performance of females during the follicular phase of the cycle may indicate that estrogen levels might have an influence on dichotic listening in women.
Keywords: auditory perception; dichotic listening; speech therapy; menstrual cycle; estrogen